Power quality impacts and mitigation measures for high penetrations of photovoltaics in distribution networks - Wolfs, Peter; Mejbaul Haque, M.; Ali, S. (2017)
© Springer International Publishing AG 2017. Island power systems often have high costs of generation in comparison to most large-scale continental power systems due to a high reliance on diesel generation. Many island systems are small with many being sub-megawatt in size. Apart from the issues of the economies of scale, the costs in island systems are increased by the difficulties of remoteness in terms of fuel delivery and access for maintenance. Island systems often have access to good renewable resources such as wind, biomass and solar resources. These have been successfully harnessed in many systems to reduce the reliance on diesel generation. Island power systems often have very high fractions of renewable energy. Many renewable technologies are now mature and reliable and the costs of solar systems have continued to reduce. The economics of the situation drive increasing interest and usage of PV systems. Some technical challenges emerge once a considerable fraction of the consumer energy is to be supplied from renewable sources. These key issues are intermittency and voltage control. Intermittency is reduced with a technology diversified and a spatially diversified portfolio of generation sources. Highly responsive backup generation, load demand control and storage are often used to compensate for the intermittent generation of renewables. Voltage can be easily controlled in new systems that are specifically designed to work with renewables. Older systems may need modifications such as partial reconstruction or the retrofitting of regulation devices.